2016
DOI: 10.1007/s12199-016-0532-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum triglyceride levels in relation to high-density lipoprotein cholesterol (TG-HDL) ratios as an efficient tool to estimate the risk of sleep apnea syndrome in non-overweight Japanese men

Abstract: Objectives Several studies have reported the association between sleep apnea syndrome and insulin resistance. Being overweight is known risk factor both for sleep apnea syndrome and insulin resistance. However, no studies have reported on the association between serum triglyceride levels in relation to high-density lipoprotein cholesterol (TG-HDL) ratios (a marker of insulin resistance) and sleep apnea syndrome accounting for body mass index (BMI) status. Methods Subjects for the present cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Shumizu et al recruited 1528 Japanese male subjects, including 241 patients with OSA. They found that OSA was associated with elevated AIP but only in normal-weight subjects (BMI < 25 kg/m 2 ) [ 18 ]. Wu et al investigated 246 male bus drivers from Taiwan.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Shumizu et al recruited 1528 Japanese male subjects, including 241 patients with OSA. They found that OSA was associated with elevated AIP but only in normal-weight subjects (BMI < 25 kg/m 2 ) [ 18 ]. Wu et al investigated 246 male bus drivers from Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Lower TC levels in the OSA group were, therefore, likely due to an increased usage of statins in these patients. In the previous studies, patients on statins were either included [ 19 , 22 ], excluded [ 21 ], or the results were adjusted for statin usage [ 18 , 23 ]. Nevertheless, excluding patients on statins did not change our conclusions on AIP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 To address this, the logarithmic ratio of high-density lipoprotein cholesterol (HDL-C) and triglycerides, the so called Atherogenic Index of Plasma (AIP) has been investigated in OSA before in several studies. [12][13][14][15] In addition, visceral fat distribution was demonstrated to be a better predictor for cardiovascular disease than the body mass index (BMI). 16 In line with this, composite indices which take into account both, lipid parameters and waist circumference, were better predictors for cardiovascular disease than single lipid components.…”
Section: Introductionmentioning
confidence: 99%